2006
DOI: 10.1007/s00330-006-0257-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced 3D MRI of lung perfusion in children with cystic fibrosis—initial results

Abstract: This paper is a feasibility study of magnetic resonance imaging (MRI) of lung perfusion in children with cystic fibrosis (CF) using contrast-enhanced 3D MRI. Correlation assessment of perfusion changes with structural abnormalities. Eleven CF patients (9 f, 2 m; median age 16 years) were examined at 1.5 T. Morphology: HASTE coronal, transversal (TR/TE/alpha/ST: 600 ms/28 ms/180 degrees /6 mm), breath-hold 18 s. Perfusion: Time-resolved 3D GRE pulse sequence (FLASH, TE/TR/alpha: 0.8/1.9 ms/40 degrees ), paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 23 publications
0
67
0
4
Order By: Relevance
“…In children with CF, perfusion defects imaged with MRI (Fig. 5b) correlated with the degree of tissue destruction (34). It seems reasonable that the reversibility of perfusion defects after a therapeutic intervention might serve as an indicator for response to therapy as well as a means to differentiate between regions with reversible and irreversible disease.…”
Section: Perfusion and Hemodynamicsmentioning
confidence: 95%
“…In children with CF, perfusion defects imaged with MRI (Fig. 5b) correlated with the degree of tissue destruction (34). It seems reasonable that the reversibility of perfusion defects after a therapeutic intervention might serve as an indicator for response to therapy as well as a means to differentiate between regions with reversible and irreversible disease.…”
Section: Perfusion and Hemodynamicsmentioning
confidence: 95%
“…Threedimensional (3D) MRI has provided the required high spatial and temporal resolution to analyze the first passage through the lungs of a bolus of MRI contrast agent. MRI lung perfusion has been used to demonstrate perfusion abnormalities in patients with CF (Eichinger et al, 2006) and emphysema (Ley-Zaporozhan et al, 2007). Fourier decomposition MRI has been introduced, enabling lung perfusion and ventilation imaging without the administration of contrast agents (Bauman et al, 2009) (Fig.…”
Section: Imaging In Respiratory Diseases: From Animal Models To Patientsmentioning
confidence: 99%
“…Typical patchy or wedge-shaped perfusion defects occur on MRI and it was shown that these areas of hypoperfusion correlate with the degree of parenchymal changes in pediatric (age range: 0 -6 years, mean age: 3.1 years) and adolescent (age range: 11 -19 years, median age: 16 years) CF patients (• ▶ Fig. 4, 5) [11,47]. Abnormal perfusion on MRI was already detected in the first year of life, with an overall prevalence of 85 % in preschool children, comparable to the aforementioned prevalence of air trapping [11].…”
Section: Parenchymamentioning
confidence: 99%